A way forward for wild fungi in international sustainability policy - Rodrigo Oyanedel; Amy Hinsley; Bryn T.M. Dentinger; E.J. Milner‐Gulland; Giuliana Furci (Conservation Letters, 2022)
Abstract A series of international sustainability policies currently in negotiation will shape biodiversity conservation for decades to come. However, discussions of current sustainability policy have a huge blind spot: the absence of Fungi, one of the eukaryotic Kingdoms. Wild fungi are a key component of natural ecosystems (e.g., through parasitic symbiosis), maintain soil fertility by decomposing organic matter, and facilitate uptake of water and nutrients through mycorrhizal association with plant roots, enhancing carbon sequestration. Moreover, the harvest, use, and trade of wild fungi are essential economic and cultural activities, supporting livelihoods and providing food and medicinal ingredients. Still, the sustainability of wild fungi use is hard to assess because there is a lack of attention from research, legislation, and society at large. Here, we present a way forward for including wild fungi in international sustainability policy. We layout four key steps to foster a much‐needed policy and societal transformation: acknowledge the existence of Fungi as an independent Kingdom; tailor sustainability policy targets to include Fungi; implement comprehensive monitoring of wild fungi status and trends; and promote responsible use of wild fungi as a livelihood opportunity in rural areas. These steps can facilitate a transition toward better recognizing, valuing, and conserving the ecosystem services wild fungi provide.